Serving the Vulnerable: The World Health Organization's Scaled Support to Countries During the First Year of the COVID-19 Pandemic - Pereira Bajard, Micaela; Stephens, Nicola; Eidman, Johan; Warren, Kathleen Taylor; Molinaro, Paul; McDonough-Thayer, Constance; Rovaletti, Rafael; Acharya, Shambhu P.; Graaff, Peter J.; Samaan, Gina (Frontiers in Public Health, 2022)
The Inter-Agency Standing Committee (IASC) serves as the global humanitarian coordination forum of the United Nations system. The IASC brings 18 agencies together, including the World Health Organization (WHO), for humanitarian preparedness and response policies and action. Early in the COVID-19 pandemic, the IASC recognized the importance of providing intensified support to countries with conflict, humanitarian, or complex emergencies due to their weak health systems and fragile contexts. A Global Humanitarian Response Plan (GHRP) was rapidly developed, which reflected the support needed for 63 target countries deemed to have humanitarian vulnerability. This paper assessed whether WHO provided intensified technical, financial and commodity inputs to GHRP countries (n=63) compared to non-GHRP countries (n=131) in the first year of the COVID-19 pandemic. The analysis showed that WHO supported all 194 countries regardless of humanitarian vulnerability. Health commodities were supplied to most countries globally (86%), and WHO implemented most (67%) of the 1.268 billion spent in 2020 at country level. However, proportionally more GHRP countries received health commodities and nearly 4 times as much was spent in GHRP countries per capita compared to non-GHRP countries (232 versus 60 per 1000 capita). In countries with WHO country offices (n=149), proportionally more GHRP countries received WHO support for developing national response plans and monitoring frameworks, training of technical staff, facilitating logistics and situation updates. This affirms WHO’s capacity to scale country support according to its humanitarian mandate. Further work is needed to assess the impact of WHO’s inputs on health outcomes during the COVID-19 pandemic.